On the Hydrophilicity and Water Resistance Effect of Styrene‐Acrylonitrile Copolymer Treated by CF4 and O2 Plasmas. Issue 10 (7th April 2015) - López‐García, Jorge; Primc, Gregor; Junkar, Ita; Lehocký, Marian; Mozetič, Miran
Abstract : A commercial formulation of styrene‐acrylonitrile copolymer (SAN) sheets were surface‐modified by using non‐thermal radiofrequency and microwave plasma treatments. In order to evaluate the possible improvement of SAN surface properties, the modification was performed using oxygen and tetraflouromethane (CF4 ) discharges under different treatment durations and output powers. The untreated and treated samples were chemically and morphologically characterised by X‐ray Photoelectron Spectroscopy (XPS) and Atomic Force Microscopy (AFM), and surface charge was evaluated by zeta potential (ζ) measurements. In addition, water contact angle measurements were employed for evaluating the extent of hydrophilicity and hydrophobicity on the treated specimens. The overall outcome indicated drastic chemical and physical surface changes, which vary according to the carrier gas. Surface became noticeably hydrophilic after few seconds of oxygen plasma treatments, whilst the surface became hydrophobic after the CF4 treatments. The present approach might serve as a feasible and promising method to alter the surface properties of styrene‐acrylonitrile copolymers. Abstract : SAN copolymers are in ever growing demand for various technological applications. This study explores O2 and CF4 plasma treatments as strategies to enhance surface properties of this polymeric material. The results presented herein highlight the potential of plasmas to extend SAN applicability, and opens the door to more in depth studies from both scientific and engineering standpoint.